A wideband low power low-noise amplifier in CMOS technology - Meaamar, Ali (2010)
A T-coil network can be implemented as a high order filter for bandwidth extension. This technique is incorporated into the design of the input matching and output peaking networks of a low-noise amplifier. The intrinsic capacitances within the transistors